2012
DOI: 10.5808/gi.2012.10.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of the Use of Public Microarray Database for Identifying Significant Genes Associated with Oral Squamous Cell Carcinoma

Abstract: There are lots of studies attempting to identify the expression changes in oral squamous cell carcinoma. Most studies include insufficient samples to apply statistical methods for detecting significant gene sets. This study combined two small microarray datasets from a public database and identified significant genes associated with the progress of oral squamous cell carcinoma. There were different expression scales between the two datasets, even though these datasets were generated under the same platforms - … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Then qRT-PCR was used to validate the most important miRNAs, which showed a two-fold upregulation for miR-494 and miR-3651 and a two-fold downregulation for miR-186. Another study with microarray data using Affymetrix U133A platform revealed that 51 genes were upregulated and found that most of genes were related to OSCC [66]. Their findings also showed a new set of OSCC-related genes (RHEB, SOD2, SKP2, IFI16, IFI44, STAT1, and GREM1) and three genes (MMP1, SOCS3, and ACOX1) that differentiate the normal tissue from the cancer [67].…”
Section: Transcriptomics-based Biomarkersmentioning
confidence: 97%
“…Then qRT-PCR was used to validate the most important miRNAs, which showed a two-fold upregulation for miR-494 and miR-3651 and a two-fold downregulation for miR-186. Another study with microarray data using Affymetrix U133A platform revealed that 51 genes were upregulated and found that most of genes were related to OSCC [66]. Their findings also showed a new set of OSCC-related genes (RHEB, SOD2, SKP2, IFI16, IFI44, STAT1, and GREM1) and three genes (MMP1, SOCS3, and ACOX1) that differentiate the normal tissue from the cancer [67].…”
Section: Transcriptomics-based Biomarkersmentioning
confidence: 97%
“…Kim et al. firstly identified Gremlin as a related gene with oral squamous cell carcinoma (OSCC), and then the roles of Gremlin in OSCC were further confirmed by other studies 20–22 . More recently, Gremlin was proved to distribute in the periodontal tissues and played a site‐specific role in regulating cell proliferation or differentiation 23 .…”
Section: Introductionmentioning
confidence: 95%
“…18 , 19 Kim et al firstly identified Gremlin as a related gene with oral squamous cell carcinoma (OSCC), and then the roles of Gremlin in OSCC were further confirmed by other studies. [20][21][22] More recently, Gremlin was proved to distribute in the periodontal tissues and played a site-specific role in regulating cell proliferation or differentiation. 23 Accordingly, all these data above bring a new perspective that gremlin may be involved in the progression of oral related inflammation, such as periodontitis, via regulating NF-κB signaling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, Kim et al identified GREM1 as an OSCCrelated gene. 12 Previous studies have suggested that GREM1 can inhibit BMP, 13 which is a member of TGF-β family [14][15][16][17] and have also suggested that interference with GREM1 expression may result in decreased TGF-β expression. 18 Insofar as GREM1 could potentially affect TGF-β signal pathway, we conducted the present study with the main objective of exploring the effects of miR-218 on OSCC and its mechanism involving GREM1 and the TGF-β signalling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, GREM1 plays an important role in certain malignancies by antagonizing bone morphogenetic proteins and regulating angiogenesis 11 . In addition, Kim et al identified GREM1 as an OSCC‐related gene 12 . Previous studies have suggested that GREM1 can inhibit BMP, 13 which is a member of TGF‐β family 14‐17 and have also suggested that interference with GREM1 expression may result in decreased TGF‐β expression 18 .…”
Section: Introductionmentioning
confidence: 99%